Sedimentary evolution during the last ~1.9 Ma near the western margin of the modern Bohai Sea - Liu, Jian; Wang, H.; Wang, F.; Qiu, J.; Saito, Y.; Lu, J.; Zhou, L.; Xu, G.; Du, X.; Chen, Q. (Elsevier BV, 2016)
© 2016. Because the Bohai Sea is a semi-enclosed sea connected to the North Yellow Sea only via the Bohai Strait, its sedimentary evolution during the Quaternary has been complex. In particular, the timing of Quaternary transgressions, especially Pleistocene transgressions, in the region, has long been a matter of controversy. Thus, the sedimentary history of the Bohai Sea in the Quaternary is still poorly understood. Borehole core YRD-1101 (200.30 m long), drilled in 2011 on the northern coast of the modern Yellow River delta, covers the last ~1.90 Ma, as indicated by paleomagnetic measurements. Here we report the results of integrated analyses of the core, including its sedimentary characteristics, downcore changes in environmental proxies (benthic foraminifers and ostracods), and accelerator mass spectrometry (AMS) 14C and optically stimulated luminescence (OSL) dates. From ~1.9 to ~0.83 Ma, the environment was fluvial. The first Quaternary transgression occurred at ~0.83 Ma (the latest Early Pleistocene), presumably caused by minor subsidence of the Miaodao Islands Uplift. Several relatively weak transgressions occurred from ~0.83 Ma to the end of the Middle Pleistocene, and three major marine sedimentary beds, here called T-3, T-2, and T-1 in ascending order, recorded in the early to middle MIS 5, the early MIS 3, and the middle to late Holocene, respectively, were presumably caused by major subsidence of the Miaodao Islands Uplift. In transgression strength, T-3 was weaker than T-2, which was basically the same as T-1. We interpret the change in transgression strength to reflect the interplay of sea-level changes, neotectonic subsidence, and sediment supply changes. Comparisons with other cores from around the Bohai Sea showed that the thickness of the Quaternary sedimentary sequence differs significantly among them, and both the T-2 and T-3 clearly display differences in thickness, facies sequence, and completeness among the cores, highlighting the important role of tectonic activity in the evolution of the Quaternary stratigraphy in the Bohai Bay Basin.